2008
DOI: 10.1080/19942060.2008.11015235
|View full text |Cite
|
Sign up to set email alerts
|

Investigation On Flow Field In Simplified Piston Bowls for Di Diesel Engine

Abstract: Three-dimensional flow calculations of the in-cylinder flow for a direct-injection Diesel engine have been carried out with different combustion chambers. In order to assess the decisive factors for the formation and evolution of the in-cylinder flow field, simplified piston bowls were used. A limited number of validation calculations of the compression stroke were performed. The results show that the geometries of the piston have a significant influence on the distribution of the cross section-averaged swirl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…From the computational fluid dynamics (CFD) simulations, it has been observed that symmetric toroidal vortices of reentrant piston bowl shape would enhance the squish-swirl and turbulence kinetic energy (TKE) during compression stroke when compared to openpiston bowl shape. Hence swirl, squish, and turbulence is strongly influenced by the piston bowl geometry in diesel engines (Payri et al, 2004;Song et al, 2008;Prasad et al, 2011). For instance, combustion chambers with bottom corners have been reported to result in improved thermal efficiency and reduced NOx, CO, and soot emissions when compared to lip shaped combustion chambers (Ghodke and Suryawanshi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From the computational fluid dynamics (CFD) simulations, it has been observed that symmetric toroidal vortices of reentrant piston bowl shape would enhance the squish-swirl and turbulence kinetic energy (TKE) during compression stroke when compared to openpiston bowl shape. Hence swirl, squish, and turbulence is strongly influenced by the piston bowl geometry in diesel engines (Payri et al, 2004;Song et al, 2008;Prasad et al, 2011). For instance, combustion chambers with bottom corners have been reported to result in improved thermal efficiency and reduced NOx, CO, and soot emissions when compared to lip shaped combustion chambers (Ghodke and Suryawanshi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From the numerical (CFD) simulations it is observed that the symmetric toroidal vortices of re-entrant piston bowl shapes will enhance the squish-swirl, turbulence kinetic energy (TKE) during compression stroke when compared to open-piston bowl shape which have bigger bowl diameter so therefore emissions will be decreased. Hence swirl, squish, turbulence are strongly influenced by the piston bowl geometry in diesel engines [25][26][27]. The combustion chamber with bottom corner will results the improved thermal efficiency and reduced NOx, CO and soot emissions when compared to lip shape and wall distance combustion chambers [28].…”
Section: Single Fuel Operation In Diesel Enginementioning
confidence: 99%
“…They indicated that simulation of the process for the gasphase flow using the proprietary code, FLUENT gives good agreement with experiment. More recently, Song et al [16] analyzed the threedimensional flow calculations of the in-cylinder flow for a directinjection Diesel engine for different combustion chambers. They showed that the geometries of the piston have a significant effect on …”
Section: Introductionmentioning
confidence: 99%